Mortality and associated risk factors in patients with severe methanol or ethylene glycol poisoning treated with dialysis : a retrospective cohort study - Kuusela, Emma (My University, 2025)
Methanol (MET) and ethylene glycol (EG) are toxic alcohols with a high mortality rate. Their toxic metabolites cause hypoxia, cytotoxicity, end-organ toxicity, and severe metabolic acidosis. Even with adequate treatment, patient survival rate is poor due to late presentation of symptoms. The aim of this study was to better understand the clinical course and mortality in adults with MET or EG poisoning. In this retrospective cohort study, data were collected from 15 MET and 13 EG patients treated in the intensive care unit (ICU) at Turku University Hospital in 2010-2019. Laboratory markers, hourly urine output and Glasgow Coma Scale were measured on admission and 24 hours after initiation of renal replacement therapy (RRT) to assess the severity of acidosis, kidney function and mental status. In addition, 90-day outcome data were collected. As a result of univariate analysis of the data, higher anion gap and lower pH, bicarbonate, base excess, and Glasgow Coma Scale score were associated with 90-day mortality. Patients with MET or EG poisoning were severely acidotic on admission with a mean pH of 7.1±0.2. Compared to MET patients, patients with EG poisoning were older and they had lower hourly urine output in the first 24 hours. In conclusion, severe metabolic acidosis, high anion gap or altered mental status on admission were associated with mortality in both MET and EG patients. Patients with EG poisoning seem to have a lower urine output.
Keywords: metanoli, etyleeniglykoli, metabolinen asidoosi, myrkytys